توظيف بعض من ألحان الرحبانية لتعليم آلة الفيولينة - موسى، سمير رشاد سيد; عبدالعزيز، محمد عصام Abdulaziz, Mohammed Essam; رضوان، آية حمدي إبراهيم (جامعة حلوان - كلية التربية الموسيقية, 2022)
استنباط تمارين تكنيكيه من ألحان الرحبانية والاستفادة منها لتعليم آلة الفيولينة للمبتدئين بسهولة، ودمج الطابع الشرقي لموسيقى الرحبانية مع تقنيات الأداء الغربي على آلة الفيولينة. يهدف هذا البحث إلى:- -إمكانية استنباط تمارين تكنيكية من ألحان الرحبانية لتعليم آلة الفيولينة للمبتدئين. -التعرف على دور الرحبانية في المسرح الغنائي والموسيقي التصويرية. -معرفة من الملحنين المصريين الذين تعاونوا مع الرحبانية. -أساليب الأداء المختلفة لآلة الفيولينه والاستفادة منها وتطبيقها في عينة البحث. ‏ويتم تقسيم البحث إلى:- أولا: الإطار النظري. ثانيا: الإطار العملي. ثالثا: النتائج والتوصيات. رابعا: قائمة المراجع. Devising technical exercises from the Rahbaniya melodies and benefiting from them for beginner violin students easily, and integrating the eastern character of Rahbaniya music with Western performance techniques on the violin This research aims to:- The possibility of devising technical exercises from Rahbaniya tunes to teach the violin for beginners. Learn about the role of Rahbaniya in musical theater and accidental music. Knowledge of the Egyptian composers who collaborated with Rahbaniya. The different technique methods of the violin and its benefits on the research samples. This research is divided into:- First: Theoretical framework. Second: Practical framework. Third: Results, recommendations. Forth: List of references.
Keywords: الآلات الموسيقية -- الرحبانيين -- الموسيقى العربية